Região, território e planejamento estatal: planejamento plurianual e desenvolvimento regional - CHAGAS, Clay Anderson Nunes (2010)
This work analyzes the discussion about the territorial dimension in the state planning. This discussion is not recent. It emerges in the worldwide scenario due to issues relating to a set of factors imposed by the flexible and globalizing process of accumulation, which aims at producing homogeneous spaces. At that moment, the State role as a promoter of development was redefined, changing its power relation in the space production, establishing therefore a power correlation with society. However, the recent plan issued in Brazil involves the resolution of crucial topics, directly linked to State intervention strategies, based on a territorial logic that has the region as its starting point. Within this framework, it is necessary to discuss the concept of region and territory inside the territorial/regional planning dynamics. The thesis presented in this work demonstrates that even with the strong efforts for the creation of PPAs, and the subsequent connecting programs, particularly when a "modern" public planning method is introduced with the territory concept and other instruments of execution and evaluation, the analysis of the program-budget shows that they follow another regional logic of resources allocation, abiding by the Federal Constitution provisions regarding final programs and the support of public policies and special areas. Therefore, the budget follows a regional dynamics while the plans and programs follow a territorial dynamics. The budget-program establishes resources allocation according to the IBGE regional division – dividing Brazil in five regions. The studies of Territorial Dimension for Planning, that guide the PPAs, particularly those of 2008 - 2011, try to establish development programs based on the creation of a number of territories. This raises a serious issue in the Brazilian public planning dynamics, which is the disjuncture between Plan – Budget – Program, denying their concept of integration.